Pengolahan Jamu Secang Jahe Sebagai Bahan Pembuatan Sorbet - Eden Pratama; Bartolomeus Herawan Mintardjo; Alip Suroto (Sekolah Tinggi Pariwisata Sahid Surakarta, 2020)
The purpose of this study was to determine the role and influence of making techniques and ingredients of ginger herbal medicine for making Sorbet. This type of research is experimantal research. Data in this study were collected by qualitative descriptive research. The data analysis technique used is the triangulation method. The results of this study are (1) sorbet characteristics tend to be rather rough, (2) the content of herbal medicine and ginger as a body warmer, (3) long shelf life, (4) cold sensation is felt when eaten and warm after being swallowed, (5) the special aroma of secang and strong ginger, (6) the resulting color is red like secang wood. In conclusion, this product will be in great demand by the general public with different consumption styles from drinking herbs in general, which are served warm. A refreshing but warm sensation of cold when swallowed as if you were not drinking herbal medicine.